Temperature response and moisture transport in damaged concrete under an atmospheric environment. (1st October 2016) - Zhang, Weiping; Min, Hongguang; Gu, Xianglin
Highlights: An analytical model was proposed for temperature response in cylindrical concrete. Damage had a significant effect on thermal conductivity and temperature response. Temperature response was obtained in damaged concrete in an atmospheric environment. Moisture transport occurred in damaged concrete caused by temperature gradient. Hysteresis time depended on thermal diffusivity, initial temperature difference and concrete size. Abstract: This paper presents an in-depth study of temperature response and moisture transport tests in damaged concrete under an atmospheric environment. Effects of concrete damage on thermal conductivity and temperature response were also investigated along with the effects of concrete damage on moisture transport caused by temperature gradient. The experimental results show that thermal conductivity of concrete decreases with the increasing damage level, and there is always a hysteresis effect for temperature response in damaged concrete. In addition, the temperature response rate in damaged concrete changes quickly at the beginning and decreases gradually with time. The greater the initial temperature difference is, the greater the initial temperature response rate is. When the temperature gradient exists on both sides of concrete, the moisture transport will occur in the heat transfer direction. Given the same initial temperature difference, the temperature response rate decreases slightly with the increasing damage level, while the moisture transport mass increases incrementally. Based on Fourier's law and the principle of energy conservation, a temperature response model was established for cylindrical concrete. This model can be used to predict temperature response in concrete with different damage levels, and the predicted results are all in acceptable agreement with the experimental values. The calculated results show that the hysteresis time is related to thermal diffusivity, the initial temperature difference and the size of the concrete specimen. Finally, the effect of damage on temperature response increases with the increasing size of the concrete specimen.